2012
DOI: 10.1093/ckj/sfs087
|View full text |Cite
|
Sign up to set email alerts
|

IgA-mediated anti-glomerular basement membrane disease: an uncommon mechanism of Goodpasture's syndrome

Abstract: Goodpasture's (GP) disease is usually mediated by IgG autoantibodies. We describe a case of IgA-mediated GP, in a patient presenting with isolated rapidly progressive glomerulonephritis. The diagnosis was established on kidney biopsy, since routine enzyme-linked immunosorbent assay (ELISA) targeted at IgG circulating autoantibodies failed to detect the nephritogenic antibodies. Immunofluorescence microscopy showed intense linear deposition of IgA along the glomerular capillary walls. An elevated titre (1:80) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…A proportion of patients who have demonstrable deposition of IgG on the GBM by immunofluorescence, but who are negative for circulating antibodies by these conventional techniques, may be positive when tested by highly sensitive biosensor assay (54). In anti-GBM disease, the pathogenic antibodies are usually of the IgG class, with IgG1 and IgG3 subclasses predominating (37,38), although rare cases of IgA-and IgG4-mediated disease have been described (55,56). These antibodies may not be detected on routine assays.…”
Section: Serologic Testingmentioning
confidence: 99%
“…A proportion of patients who have demonstrable deposition of IgG on the GBM by immunofluorescence, but who are negative for circulating antibodies by these conventional techniques, may be positive when tested by highly sensitive biosensor assay (54). In anti-GBM disease, the pathogenic antibodies are usually of the IgG class, with IgG1 and IgG3 subclasses predominating (37,38), although rare cases of IgA-and IgG4-mediated disease have been described (55,56). These antibodies may not be detected on routine assays.…”
Section: Serologic Testingmentioning
confidence: 99%
“…Speculatively, this type of analysis may have been able to detect circulating antibodies in the cases reported by Dash et al [ 3 ] and Kussman and Gohara [ 4 ]. Alternatively, as in the case reported by Moulis et al [ 2 ] and the 11 similar cases reviewed in their discussion, ELISA testing for IgG anti-GBM autoantibodies was negative because the disease was mediated by IgA autoantibodies. Anti-GBM nephritis thus exemplifies the glomerular disease whose firm diagnosis relies on a combination of clinical, serologic and histopathologic findings.…”
mentioning
confidence: 89%
“…These unusual cases of RPGN were instances in which the diagnosis could only be made by a kidney biopsy. Moulis et al [ 2 ], Dash et al [ 3 ] and Kussman and Gohara [ 4 ] all describe classic clinical presentations of RPGN with negative serologic testing for circulating anti-GBM IgG autoantibodies (as well as negative testing for other causes of RPGN, such as ANCA and lupus) but firm diagnoses of anti-GBM nephritis made by kidney biopsies. Interestingly, the case reported by Moulis et al [ 2 ] showed on IF linear staining that was stronger for IgA than for IgG, prompting the authors to re-test their patients for anti-GBM IgA autoantibodies, which were positive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Goodpasture's syndrome (GPS) is an immuno disorder characterized by pulmonary hemorrhage, glomerulonephritis and the presence of the antiglomerular basement membrane (anti-GBM) antibody (1,2). The incidence of GPS is <1 case/1,000,000 (3).…”
Section: Introductionmentioning
confidence: 99%